Evaluation Capacity Development through Cluster Evaluation - Khalil Bitar; Rola Hbeichi; Lamia Al-Zou'bi; Craig Russon (The Evaluation Center at Western Michigan University, 2014)
Background:  The term "cluster evaluation" was first coined in 1988 by W. K. Kellogg staff in an evaluation of a Foundation-funded initiative; the concept was further developed and practiced by the Kellogg Foundation evaluation consultants and other practitioners in the evaluation community   Setting:  Cluster evaluation was a model used to evaluate the programming of a small specialized UN agency in three countries (Lebanon, Jordan and Palestine) of the Arab States.   Purpose: The article explains how cluster evaluation, as originally conceived by the W. K. Kellogg Foundation, was adapted to the realities of the UN system.   Subjects: NA   Research Design:  The authors present a case study of an evaluation of a cluster of programmes from the Arab States region (Lebanon, Jordan and Palestine) that was conducted by a small, specialized agency of the UN.   Data Collection and Analysis: The evaluation was designed as a series of programme reviews. Information from the reviews was to be aggregated in order to understand collective contributions to the region.   Findings: The case study demonstrates the potential benefits of the model as well as some of the challenges.   Conclusions:  Analysis of the data leads to a number of interesting conclusions. First, in the philanthropic sector, cluster evaluation is a programmatic intervention. That is not the way that the model was used in the context of this evaluation. Instead of evaluation as intervention, it was evaluation as capacity development.   This evaluation took place in the Arab States, a region in which evaluation capacity is perhaps not as institutionalized as other parts of the world. The purpose of using a cluster evaluation in this context was to strengthen the capacities of the national evaluators.   Each of the national evaluators who were contracted had different areas of strength and weakness. By establishing a strong network amongst themselves, they were able to leverage each other's strength and to compensate for any weaknesses.   The consultants developed each other's capacity and that greatly benefited the evaluation. The higher capacity went on to benefit the collective evaluation capacity of the region. The national evaluators have all gone one to be leaders in the formation of their respective regional and national evaluation organisations.